Home Along the Railway: Understanding the Migration and Settlement of Informal Settler Families Living Along Railway Lines in the Philippines - Inero Ancho; Gabrielle Louis David; Ferlynn Recto; Sue Liza Saguiguit; Daisy Pelegrina (Journal of Asian Social Science Research, 2025)
This study investigates the living conditions of Filipino informal settler families (ISFs) residing along the Philippine National Railways (PNR) tracks in Brgy San Antonio, Los Baños. It examines their past through migration histories, their present through unmet basic needs, and their aspirations amid an uncertain future. Utilizing a narrative approach, the research draws on semi-structured interviews and field observations to collect qualitative data. Findings reveal that economic vulnerability is the primary driver behind their settlement along the rail tracks. The persistent threat of eviction discourages residents from investing in housing improvements, while access to essential services remains limited. Nevertheless, strong social ties and support from the barangay contribute to community cohesion. The study concludes that inadequate urban planning and weak enforcement of housing policies have contributed to the persistence of informal settlements. It calls for the implementation of inclusive and sustainable relocation programs that genuinely respond to the needs and aspirations of ISFs.